2020
DOI: 10.11646/zootaxa.4878.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Indoreonectes telanganaensis, a new species of loach (Teleostei: Nemacheilidae) from the Godavari Basin of India

Abstract: A new species of hill-stream loach, Indoreonectes telanganaensis, is described from a seasonal tributary of the Godavari River at Maisamma Loddi, within the Kawal Tiger Reserve, Telangana State, India. The new species is distinguished from its congeners by a combination of characters including caudal peduncle as long as deep; eye large, its diameter about one-fifth head length; pectoral fin as long as head; nasal barbel reaching the middle of the eye; dorsal-fin origin on vertical through pelvic-fin origin; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…In the current study we redescribe Indoreonectes evezardi from its type locality using fresh collections and specimens studied by Prasad et al (2020). Further, we describe two new species from the I. evezardi complex from the Mula River, a tributary of the Godavari river system and from the Hiranyakeshi River, part of the Krishna river system.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the current study we redescribe Indoreonectes evezardi from its type locality using fresh collections and specimens studied by Prasad et al (2020). Further, we describe two new species from the I. evezardi complex from the Mula River, a tributary of the Godavari river system and from the Hiranyakeshi River, part of the Krishna river system.…”
Section: Introductionmentioning
confidence: 99%
“…The genus is diagnosed based on following combination of characters following Rita et al (1978) and, Bănărescu and Nalbant (1995): nostrils close to each other, posterior one distant from eye; lateral line present, short; length of nasal barbels variable; free posterior part of air bladder rudimentary; bars on side of body. Currently, the genus is represented by three species, I. evezardi (Day, 1872), I. keralensis (Rita and Nalbant, 1978) and I. telanganaensis (Prasad, Srinivasulu, Srinivasulu, Anoop and Dahanukar, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last few years, several new species of fish were described from this region. This includes a new species of bagrid catfish Rita bakalu from Pranahita River (Lal et al 2017) and a new species of hillstream loach Indoreonectes telanganaensis (Prasad et al 2020b). Prasad & Srinivasulu (2019a,b) provided new records of fishes from Telangana State, while Shyamsundar et al (2017) and Prasad et al (2020a) reported the checklist of freshwater fish fauna in the Udayasamudram and Manjeera reservoirs, respectively.…”
mentioning
confidence: 99%